Kebijakan Hutang dan Keputusan Investasi sebagai Determinan Nilai Perusahaan: Bukti pada Sektor Transportasi Darat Indonesia - Octaria, Rani; Salma, Nur; Hasbullah, Hasbullah (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2025)
Maintaining firm value is a strategic problem in Indonesia's capital-intensive land transportation business, which is also extremely vulnerable to demand shocks, fuel prices, and infrastructure expenses. There is currently little data on how internal finance policies affect business value in this particular industry because most prior research has employed mixed-industry samples. This study examines how investment choices and debt policies affect the firm value of land transportation businesses listed between 2020 and 2024 on the Indonesia Stock Exchange (IDX). Data from seven companies (35 firm-year observations) were gathered from audited financial statements using a quantitative method, and SPSS 26 was used for multiple linear regression analysis. The Debt to Assets Ratio (DAR), Price Earnings Ratio (PER), and Price to Book Value (PBV) serve as proxies for debt policy, investment decisions, and company value, respectively. The findings indicate that while investment choices do not significantly affect business value, debt policy does have a positive and significant impact. Nonetheless, investment choices and debt policies work together to significantly impact business value, accounting for 60.4% of the variance. These results demonstrate how crucial financing structure is to value creation in capital-intensive land transportation companies and suggest that management should maximize leverage use while better informing the market about long-term investment plans.